GPS x GNSS: GLONASS constellation by maximizing the precision and accuracy of data - Prina, Bruno Zucuni; Trentin, Romario (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In this paper was compared the GNSS data post-processing, analyzing the result of the processing of data with the GPS constellation and, later, with the addition of GLONASS constellation. The points analysed are located in the urban perimeter of the municipality of Jaguari/RS and were collected by relative positioning method fast static. A total of 108 points were analyzed, and the same were postprocessed in Topcon Tools® application subsequently the data were statistically analyzed by means of a spreadsheet (Excel ®). Thus, compared to the RMS of the points (horizontal and vertical), the coordinates (planimetric and altimetry), the number of satellites and the solution of the points in both software. Thus, notified that with the junction of GLONASS data with the GPS there is a significant gain in the precision and accuracy of the post-processed data.